Ecological, Economical and Social Sustainability of Organic Farming (Indian Journal of Extension Education, 2019)
The study was conducted in Bengaluru rural and Chikkballapur district of southern Karnataka to assess the sustainability of organic farming. Data were collected from 120 organic farmers. Ex post facto research design was employed for the study. More than 47 per cent of the respondents opined that organic farming was highly sustainable. With respect to ecological sustainability of organic farming, 47.50 per cent of respondents observed that organic farming was highly sustainable whereas economical sustainability of organic farming was stated by 52.50 per cent of respondents. More than 47 per cent of organic farmers considered organic farming socially sustainable.